2021
DOI: 10.1155/2021/9976738
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Relationship between the Natural Frequency and the Corrosion in Reinforced Concrete Beams

Abstract: Due to many nondamage factors such as temperature, humidity, carbonation, and corrosion effects on natural frequency, the key problem of the application frequency-based method to detect damage is to reveal the rules of these factors affect natural frequency and further to eliminate their effects. The long-term characteristics of reinforced concrete structures require a lot of attention, especially in corrosive environment. In this paper, an experimental investigation was conducted to study the deflection and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Furthermore, the results show a clear decreasing trend since all values are derived from a single beam which was tested at different CLs. Finally, Zhang et al 49 reported a relatively large decrease in f 1 with respect to the low CL. However, Figure 3 only shows the CL of the main reinforcement while the stirrups of the beams tested by Zhang et al 49 reached more than double the CLs of the main reinforcement.…”
Section: Discussion On Experimental Results Reported In the Literaturementioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, the results show a clear decreasing trend since all values are derived from a single beam which was tested at different CLs. Finally, Zhang et al 49 reported a relatively large decrease in f 1 with respect to the low CL. However, Figure 3 only shows the CL of the main reinforcement while the stirrups of the beams tested by Zhang et al 49 reached more than double the CLs of the main reinforcement.…”
Section: Discussion On Experimental Results Reported In the Literaturementioning
confidence: 91%
“…Finally, Zhang et al 49 reported a relatively large decrease in f 1 with respect to the low CL. However, Figure 3 only shows the CL of the main reinforcement while the stirrups of the beams tested by Zhang et al 49 reached more than double the CLs of the main reinforcement. Furthermore, it should be noted that the change in f 1 for the experiments of Zhang et al 49 is calculated relative to the natural frequency after 20 days of corrosion since no initial reference value was obtained from a non-corroded beam.…”
Section: Discussion On Experimental Results Reported In the Literaturementioning
confidence: 91%
See 3 more Smart Citations